Dietary Vitamin A Impacts Refractory Telogen - Suo, Liye; VanBuren, Christine; Hovland, Eylul Damla; Kedishvili, Natalia Y.; Sundberg, John P.; Everts, Helen B. (Frontiers in Cell and Developmental Biology, 2021)
Hair follicles cycle through periods of growth (anagen), regression (categen), rest (telogen), and release (exogen). Telogen is further divided into refractory and competent telogen based on expression of bone morphogenetic protein 4 (BMP4) and wingless-related MMTV integration site 7A (WNT7A). Retinoic acid synthesis proteins localized to the hair follicle and excess retinyl esters arrested hair follicles in telogen. The purpose of this study was to further define these hair cycle changes. BMP4 and WNT7A expression was used to distinguish refractory telogen in C57BL/6J mice fed different levels of retinyl esters from two previous studies. These two studies produced opposite results; and differed in the amount of retinyl esters the dams consumed and the mouse age when the different diet began. There were a greater percentage of hair follicles in refractory telogen both when mice were bred on an unpurified diet (study 1) and consumed excess levels of retinyl esters starting at 12 weeks of age, as well as when mice were bred on a purified diet containing adequate levels of retinyl esters (study 2) and remained on this diet at 6 weeks of age. WNT7A expression was consistent with these results. Keratin 6 (KRT6) and cellular retinoic acid binding protein 2 (CRABP2) localized almost exclusively to refractory telogen hair follicles in study 1. However, KRT6 and CRABP2 localized to both competent and refractory telogen hair follicles in study 2. This suggests that vitamin A may contribute to the inhibition of HFSC during refractory telogen in a dose dependent manner.